Conciliation emploi-famille et temps de travail : Que faire pour faciliter la gestion de carrière des mères et des pères ? - Tremblay, Diane-Gabrielle (Canadian Journal of Counselling and Psychotherapy, 2007)
We conducted a study on sources of difficulty in work-family balance and obtained responses from over a thousand respondents (1,045) from various occupational categories and business lines, two thirds of which were women. We were able to identify variables that may influence the difficulties of fathers and mothers in the workplace and to identify factors that may facilitate improved balance between work and family obligations, as well as the realization of individual career aspirations.